2001
DOI: 10.1007/s001980170119
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Diet to Lower Serum Cholesterol Level is a Risk Factor for Postmenopausal Osteoporosis and Distal Forearm Fracture

Abstract: The purpose of this study was to assess whether dietary changes aimed at reducing serum cholesterol can increase the risk of osteoporosis (OP) and fracture. The study group consisted of 311 postmenopausal women with high serum cholesterol levels and following a diet low in dairy products (calcium intake estimated at less than 300 mg/day) for 27.3 +/- 29.1 months. This sample was compared with a case-control group of 622 healthy postmenopausal women paired for age and age at menopause and with a calcium intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…In all subjects, a detailed personal and familial history and a previously validated questionnaire regarding the propensity to fall and the calcium daily intake were collected [24].…”
Section: Methodsmentioning
confidence: 99%
“…In all subjects, a detailed personal and familial history and a previously validated questionnaire regarding the propensity to fall and the calcium daily intake were collected [24].…”
Section: Methodsmentioning
confidence: 99%
“…Calcium intake was lower in the hypercholesterolemia group, but not in the high-Lp(a) group, probably due to the decrease in dairy foods secondary to low-fat diet [7,21,22] and it is suggested that the restriction in calcium intake due to low-fat diet may be responsible for low bone mass [21]. In a casecontrol study comparing 311 postmenopausal women with hypercholesterolemia following a low-fat diet with low dairy calcium intake (<214 mg/day) with 622 healthy postmenopausal women with high dairy calcium intake (>857 mg/day), the prevalence of lumbar osteoporosis was higher in the, hypercholesterolemia group (42.1% vs. 22.3%) suggesting the authors that the restriction in calcium intake due to the low-fat diet may have been responsible for low bone mass [21].…”
Section: Discussionmentioning
confidence: 98%
“…In all patients, the presence of previous fragility fractures was ascertained by self-report and no additional validation of this information was conducted. Calcium intake, expressed as milligrams per day, was assessed using a validated questionnaire (26). In particular, usual calcium intake coming from some selected calcium-rich foods (milk and dairy products) was estimated by a 7-day food frequency questionnaire.…”
Section: Study Design Population and Inclusion/ Exclusion Criteriamentioning
confidence: 99%
“…To standardize the slice weight, three cardboard samples of different sizes were used (about 100, 50 and 25 g). The number of standardized servings was assessed, each containing w300 mg of calcium (a 250 ml cup of milk or yoghurt, a portion of about 100 g of cottage cheese, a 50 g slice of soft cheese and a 25 g slice of aged cheese) (26). In all patients height and weight were measured and BMI was calculated.…”
Section: Study Design Population and Inclusion/ Exclusion Criteriamentioning
confidence: 99%